2018
DOI: 10.1016/j.idcr.2018.e00432
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation as a potential way to eradicate multiresistant microorganisms

Abstract: Multiresistant microorganism infection often can produce a life-threatening situation. We report two cases in which fecal microbiota transplantation used for the treatment of recurrent Clostridium difficile infection were effective in eradicating colonization by carbapenemase-producing Enterobacteriaceae. The presented cases illustrate the potential benefit of fecal microbiota transplantation in resolution of asymptomatic carrier states of multiresistant microorganisms, suggesting the need for further investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Subsequently, 6 articles were excluded after a full-text review. Finally, a total of 20 articles were selected: 10 single cases [25][26][27][28][29][30][31][32][33][34], 3 case series comprising 10 cases [35][36][37], and 7 prospective studies comprising 101 cases [38][39][40][41][42][43][44]. Of these articles, only one was a randomized controlled trial.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 6 articles were excluded after a full-text review. Finally, a total of 20 articles were selected: 10 single cases [25][26][27][28][29][30][31][32][33][34], 3 case series comprising 10 cases [35][36][37], and 7 prospective studies comprising 101 cases [38][39][40][41][42][43][44]. Of these articles, only one was a randomized controlled trial.…”
Section: Study Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…Data on 101 patients from 7 articles [37][38][39][40][41][42][43] are shown in Table 2. From the data presented in 5 studies, the median age of included patients was 65 years (IQR, 56 -76 years), and 52.5% of patients were male.…”
Section: Outcomes Of Microbiological Eradication In Prospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal microbiota transplants (FMTs) are one method that can restore the colonization resistance that is lost when the community is disrupted. Indeed, numerous published works have shown that FMT is able to restore the healthy and diverse microbial community of the gut and decrease the number of pathogens and antibiotic resistant bacteria in the intestine of both mice and humans [9][27]. FMT is a very promising therapy for decolonization and infection prevention, but it will be operationally challenging to use FMT as a prophylactic therapy on all patients who are at risk for infection.…”
Section: Introductionmentioning
confidence: 99%